Position and Authority of the Constitutional Court as a State Institution - Riyah, Juwai (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Constitutional Court of the Republic of Indonesia is the highest state institution with the same position as the Supreme Court (MA). Initially, the Constitutional Court was an institution intended only to examine the constitutionality (constitutional review) of a law against the constitution. Because of this, the constitutional court is often referred to as